CLIC1 down-regulates Nrf2/HO-1 signalling pathway promoting the apoptosis and pyroptosis in OGD/R-treated HT22 cells - Jingtong Xiong; Shuo Li; Honghai Chen; Chuanwen Yu; Yuhai Cao; Xiaofeng Qu; Jianlin Wu; Aodan Zhang; Chuang Sun (PLoS ONE, 2025)
Cerebral ischemia–reperfusion injury (CIRI) occurs during the treatment of ischemic stroke when the affected blood vessels are recanalized and the oxygen supply to the brain is restored. Chloride intracellular channel 1 (CLIC1) and the nuclear factor erythroid-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) pathway have been implicated in many neurological disorders. However, the exact mechanism by which CLIC1 contributes to CIRI remains unclear, and its potential role in modulating the Nrf2/HO-1 signaling pathway in CIRI has yet to be explored. We investigated the potential roles of CLIC1 in CIRI using an oxygen and glucose deprivation/reoxygenation (OGD/R) model in HT22 cells. The findings of our study indicated that CLIC1 was high-expressed after OGD/R and had an inhibitory effect on the Nrf2/HO-1 signalling pathway. This process led to an exacerbation of apoptosis due to oxidative stress and an increase in the activity of the nucleotide-binding oligomeriation domain-like receptor protein 3 (NLRP3) inflammasome and pyroptosis in OGD/R-treated HT22 cells. These effects were reversed when CLIC1 was silenced. Together, the results of this study confirm our hypothesis that CLIC1 promotes CIRI by suppressing the Nrf2/HO-1 signalling pathway. CLIC1 emerges as a promising therapeutic target to prevent neuronal cell injury in CIRI.